THE IMPORTANCE OF OPTOMETRY SERVICES DURING MOVEMENT CONTROL ORDER - Md-Muziman-Syah, Md Mustafa (International Journal of Allied Health Sciences, 2021)
On 11 March 2020, the World Health Organization (WHO) announced COVID-19 as a pandemic, continuing the possibility of further global outbreak. Malaysia’s government reacted with the implementation of the movement control order (MCO) 1.0 starting from 18 March 2020 as an effort to flatten the curve of COVID-19 cases in the country. Most of the economic sectors have been suspended except for essential services which include healthcare. Although optometrist is one of the healthcare professionals, optometry services in the private sector are ordered to remain closed to the public. The Association of Malaysian Optometrists (AMO) took a prompt initiative by conducting a quick survey on public perspective towards the importance of optometrist roles. This presentation will share the outcome of the survey including vision and eye problems encountered by the public during the MCO.